Estimating and measuring - Schultz-Ferrell, Karren; Weiskopf, Cathy; Powley, Linda; Kerr, Tom (New York : Barron's, 2008)
Lostis Marbles, the mayor of Mathopolis, gets math help from Elexus Estimator -- quick at estimating volume, height, weight, and other quantities -- and Maverick Measurer, who values mathematical accuracy.
1000
Keywords: Estimation theory -- Juvenile literature